(untitled) (International Journal of Engineering and Computer Science, 2013)
A hazardous effect on male fertility may be manifested by a decrease in the amount of sperm cells, disorders in their mobility, as well as structure. In this study; the analysis has been done on the impact of electromagnetic radiations on the male sperm infertility by considering the radiations from broadcasting antenna to the testis by variations of electromagnetic field with the distance from the broadcasting towers. It was found that; there is significant effects brought by radiations for those who are living close to the broadcasting towers due to the fact that electromagnetic energy from towers are being converted into thermal (heat) energy which is absorbed by the testis issues and hence cause the sperm infertility in terms of sperm count, sperm motility and any other associated effects. The SAR values was observed to decrease as one moves far away from the towers. So regulatory authorities should set safe distance before broadcasting operators erect/build their broadcasting infrastructures.